(untitled) (Journal of the College of Basic Education, 2022)
This study necessitated examining the most important Iraqi literary figures, namely the personality of Dr. Daoud Salloum. So we shed light on Dr. Daoud Salloum’s study of the image of women in literary production, and how poets employed them throughout the ages, so the images of women in the pre-Islamic era and the importance and role of Islam in the life of women, which brought about many changes He freed her from restrictions and provisions and dealt with the creative aspect of women being a critic and poet, so he presented the image of women in modern literature by presenting a group of poets, namely Al-Jawahiri, Al-Sayyab, Nizar Qabbani and the Iraqi saint Atika Al-Khazraji. That liberation falls on the part of the body and clothing.